High-strength and high-toughness SiCf-Si3N4-Si composite ceramic as well as preparation method and application thereof
Through the impregnation method and high-temperature and high-pressure pneumatic sintering process, Si powder, Al2O3 powder and phenolic resin powder are combined with silicon carbide fiber cloth, which solves the problems of high preparation cost, complex process and poor mechanical properties of silicon carbide fiber composite materials in the prior art, and realizes SiCf-Si3N4-Si composite ceramics with high strength, high toughness and low dielectric constant, which are suitable for mobile phone backplanes and other applications.
Patent Information
- Application Number
- CN202411809478.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-01
AI Technical Summary
It is difficult to develop a silicon carbide fiber composite material with low cost, simple preparation process, high efficiency and excellent mechanical properties, especially in the demand for mobile phone back panel materials.
Si powder, Al2O3 powder and phenolic resin powder were combined with the pretreated silicon carbide fiber cloth by impregnation method, and a high-temperature and high-pressure pneumatic sintering process was used to form SiCf-Si3N4-Si composite ceramics.
The prepared SiCf-Si3N4-Si composite ceramic has high strength, high toughness, low dielectric constant and high relative density, and is suitable for mobile phone backplanes and other fields.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic materials, and more specifically, relates to a high-strength and high-toughness SiCf-Si3N4-Si composite ceramic and a preparation method and application thereof. Background Art
[0002] As a high-performance non-metallic material, silicon carbide fiber has shown wide application potential in many fields due to its unique physical and chemical properties. In the mobile phone industry, ceramics are gradually gaining attention as a material for the back panel of mobile phones. The back panel of a mobile phone should not only have good mechanical properties, such as high strength, high hardness and wear resistance, but also excellent electrical insulation and thermal conductivity, as well as a beautiful appearance. Although traditional mobile phone back panel materials such as plastic, metal and glass perform well in some aspects, they are difficult to meet the needs of the high-end market in terms of comprehensive performance. In recent years, some well-known mobile phone manufacturers at home and abroad have successively launched some mobile phones with ceramic back panels, mainly zirconium oxide. Compared with zirconium oxide, the mechanical properties of silicon carbide fiber may be poor, but the SiCf-Si3N4-Si composite material generated by adding silicon powder through impregnation and gas pressure sintering has a relatively small dielectric constant, higher bending strength, and good impact resistance and thermal shock resistance. At the same time, the density of SiCf-Si3N4-Si material is only 2.9g / cm 3 , compared to 6g / cm2 of zirconium oxide 3 It is much smaller, so the corresponding mobile phone back panel is lighter, which is convenient for us to carry and use in daily life. f -Si3N4-Si material has become an ideal alternative material due to its excellent performance.
[0003] SiC f- The preparation of Si3N4-Si composite materials usually includes three main steps: raw material preparation, preform preparation and sintering. The raw material preparation is to obtain a mixed slurry by ball milling and ultrasound according to a specific ratio. The preform preparation is to immerse the silicon carbide fiber in the slurry by the impregnation method, and then obtain the preform after pressure maintenance, drying and curing. The sintering process is to better combine silicon powder and silicon carbide fiber under high temperature and high pressure to form a dense ceramic body. This process is crucial to the final performance of the material.
[0004] At present, the research on high-strength silicon carbide fiber mainly focuses on improving its strength and toughness through different preparation processes and preparation of composite materials. Li Wei et al. pretreated silicon carbide fiber, constructed a graphite layer in situ on the surface, and directly sintered the fiber using a hot pressing sintering process. The bending strength of the test sample obtained was 320MPa and the fracture toughness was 9.5MPa·m 1 / 2, but it is not suitable for large-scale production. The PEEK / SiCf composite prepared by Liu Lei et al. has a flexural strength of 130.4MPa and a fracture toughness of 7.39MPa·m 1 / 2 , but its mechanical properties are not very ideal. Therefore, it is urgent to develop a silicon carbide fiber composite material with low cost, simple preparation process, high efficiency and excellent mechanical properties. Summary of the invention
[0005] In order to solve the above-mentioned shortcomings and disadvantages of the prior art, the present invention aims to provide a high-strength and high-toughness SiC f -Si3N4-Si composite ceramics. This ceramic has excellent mechanical properties and dielectric constant.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned SiCf-Si3N4-Si composite ceramic with high strength and high toughness.
[0007] Another object of the present invention is to provide an application of the above-mentioned high-strength and high-toughness SiCf-Si3N4-Si composite ceramic.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A high-strength and high-toughness SiC f -Si3N4-Si composite ceramics are prepared by adding Si powder, Al2O3 powder and phenolic resin powder into anhydrous ethanol for mixed ball milling to obtain Si-Al2O3-phenolic resin impregnation slurry; the pretreated silicon carbide fiber cloth is completely immersed in the Si-Al2O3-phenolic resin impregnation slurry, and then vacuuming is performed, a protective gas with a pressure of 4 to 10 MPa is introduced and the pressure is maintained, drying and curing is performed at 80 to 150° C., and the obtained preform is heated to 1800 to 1900° C. and sintered under a nitrogen pressure of 1 to 10 MPa.
[0010] Preferably, the relative density of the SiCf-Si3N4-Si composite ceramic is above 95%, the bending strength is 400-600 MPa, and the fracture toughness is 7-9 MPa·m 1 / 2 , hardness is 16~18GPa, and dielectric constant is 5~8.
[0011] Preferably, the purity of the Si powder is above 99wt%, and the average particle size is 1-10μm; the purity of the Al2O3 powder is above 99.8wt%, and the particle size is 50-100nm; the purity of the phenolic resin powder is above 98wt%, and the average particle size is 10-50μm.
[0012] Preferably, the volume ratio of the Si powder, Al2O3 powder and phenolic resin powder is (20-30):(1-5):(1-5); the volume ratio of the total volume ratio of the Si powder, Al2O3 powder and phenolic resin powder to the pretreated silicon carbide fiber cloth is (11-20):(30-35).
[0013] The high strength and high toughness SiC f- The preparation method of Si3N4-Si composite ceramic comprises the following steps:
[0014] S1. Si powder, Al2O3 powder and phenolic resin powder were added to anhydrous ethanol and mixed and ball-milled to obtain Si-Al2O3-phenolic resin impregnation slurry;
[0015] S2. The pretreated silicon carbide fiber cloth is completely immersed in the Si-Al2O3-phenolic resin impregnation slurry, and then evacuated, a protective gas with a pressure of 4 to 10 MPa is introduced and the pressure is maintained, and dried and cured at 80 to 150 ° C to obtain a preform;
[0016] S3. The preform is heated to 1800-1900°C and sintered under a nitrogen pressure of 1-10 MPa to obtain a high-strength and high-toughness SiC f -Si3N4-Si composite ceramics.
[0017] Preferably, the ball milling speed in step S1 is 200-250 r / min, and the ball milling time is 24-36 h.
[0018] Preferably, the protective gas in step S2 is nitrogen or argon; and the pressure holding time is 30 to 60 minutes.
[0019] Preferably, the heating rate in step S3 is 5-15° C. / min, and the sintering time is 1-4 h.
[0020] The application of the high-strength and high-toughness SiCf-Si3N4-Si composite ceramic in the field of preparing mobile phone back panels.
[0021] The present invention uses acupuncture and other methods to preliminarily fix the stacked fiber cloths so that the relative positions between them remain stable. Then, a mixed slurry added with Si powder, Al2O3, and phenolic resin is impregnated into the gaps of silicon carbide fibers by an impregnation method to form a preform. The impregnation method can make silicon powder and other substances evenly penetrate into the pores of silicon carbide fibers, thereby enhancing the bonding force between the two. The cured prepreg is cut, trimmed, and processed as needed to form the required shape and size, and then placed in a gas pressure sintering furnace. After the temperature is raised to 1800-1900°C, the high temperature and high pressure conditions help the silicon powder to wet and diffuse on the surface of the silicon carbide fiber cloth, thereby forming a firm interface and obtaining a high-strength and high-toughness SiCf-Si3N4-Si composite ceramic.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention adopts an impregnation method and a high temperature and high pressure gas pressure sintering process to add silicon powder to the silicon carbide fiber through the impregnation method to generate SiC f -Si preform, and then sintered under high temperature and high pressure in nitrogen environment, so that Si powder forms liquid phase to fill pores, improve density and performance uniformity, and at the same time Si powder reacts with N2 to form Si3N4 at the connection with silicon carbide fiber, thus preparing high strength and high toughness SiC f- Si3N4-Si composite ceramics.
[0024] 2. The SiCf-Si3N4-Si composite ceramic prepared by the present invention has excellent mechanical properties (flexural strength and fracture toughness) and low dielectric constant, with a relative density of more than 95%, high flexural strength (400-600MPa), high fracture toughness (7-9MPa·m 1 / 2 ), a small dielectric constant (5 to 8), and mass production can be achieved. The composite ceramic can be used in the field of mobile phone back panels. DETAILED DESCRIPTION
[0025] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0026] Example 1
[0027] 1. Si powder (purity of 99wt% or more, particle size of 5μm), Al2O3 powder (purity of 99.8wt% or more, particle size of 100nm), phenolic resin powder (purity of 98wt% or more, average particle size of 20μm); add anhydrous ethanol to Si powder, Al2O3 powder and phenolic resin powder in a volume ratio of 25:5:5, mix and ball mill, put into a vacuum container, perform ultrasonic treatment, remove bubbles and volatile substances in the slurry, and obtain Si-Al2O3-phenolic resin impregnation slurry;
[0028] 2. The silicon carbide fiber cloth (plain weave, silicon carbide content not less than 90%, diameter of 10-20 μm. The weaving density is moderate, and the number of warp and weft lines per centimeter is about 10-30) is cleaned, cut, and stacked for pretreatment, and the pretreated silicon carbide fiber cloth and Si-Al2O3-phenolic resin impregnation slurry with a volume ratio of 65:35 are placed in a vacuum impregnation tank so that the fiber cloth is completely immersed in the slurry, and then the impregnation tank is evacuated and maintained for 30 minutes, and then 5MPa nitrogen is introduced into the impregnation tank and the pressure is maintained for 30 minutes, and it is dried and cured at 80°C to obtain a preform.
[0029] 3. The preform was placed in a gas pressure sintering furnace, heated to 1850°C and sintered at a nitrogen pressure of 5 MPa for 4 hours to obtain SiCf-Si3N4-Si composite ceramics.
[0030] The relative density of the SiCf-Si3N4-Si composite ceramic prepared in this embodiment is 98.2%, the flexural strength is 588 MPa, and the fracture toughness is 8.5 MPa·m 1 / 2 , hardness is 18 GPa, and dielectric constant is 6. This indicates that the SiCf-Si3N4-Si composite ceramic has excellent mechanical properties (flexural strength, fracture toughness) and low dielectric constant.
[0031] Comparative Example 1
[0032] The difference from Example 1 is that in step 1, Si powder and Al2O3 powder with a volume ratio of 25:10 are added to anhydrous ethanol, mixed and ball-milled, placed in a vacuum container, and ultrasonically treated to obtain Si-Al2O3 impregnation slurry. In step 2, the pretreated silicon carbide fiber cloth and Si-Al2O3 impregnation slurry with a volume ratio of 65:35 are prepared;
[0033] The relative density of the SiCf-Si3N4-Si composite ceramic prepared in this embodiment is 88.2%, the flexural strength is 189 MPa, and the fracture toughness is 4 MPa·m 1 / 2 , hardness is 15GPa and dielectric constant is 8.
[0034] Example 2
[0035] The difference from Example 1 is that: in step 1, Si powder, Al2O3 powder and phenolic resin powder in a volume ratio of 20:5:5 are added to anhydrous ethanol and mixed and ball-milled, and the impregnation slurry is placed in a vacuum container and ultrasonically treated to obtain an impregnation slurry of Si-Al2O3-phenolic resin; in step 2, the impregnation slurry of pretreated silicon carbide fiber cloth and Si-Al2O3-phenolic resin in a volume ratio of 70:30 is obtained.
[0036] The relative density of the SiCf-Si3N4-Si composite ceramic prepared in this embodiment is 95.9%, the flexural strength is 453 MPa, and the fracture toughness is 6.8 MPa·m 1 / 2 , hardness is 16GPa and dielectric constant is 7.
[0037] Example 3
[0038] The difference from Example 1 is that in step 1, Si powder (purity of more than 99wt%, average particle size of 0.5μm), Al2O3 powder (purity of more than 99.8wt%, particle size of 50-100nm), and phenolic resin powder (purity of more than 98wt%, average particle size of 10-50μm), Si powder, Al2O3 powder and phenolic resin powder in a volume ratio of 30:5:5 are added to anhydrous ethanol and mixed and ball-milled, placed in a vacuum container, and ultrasonically treated to obtain an impregnation slurry of Si-Al2O3-phenolic resin, and in step 2, the pretreated silicon carbide fiber cloth and Si-Al2O3-phenolic resin are impregnated in a volume ratio of 60:40.
[0039] The relative density of the SiCf-Si3N4-Si composite ceramic prepared in this embodiment is 97.7%, the flexural strength is 512MPa, and the fracture toughness is 7.7MPa·m 1 / 2 , hardness is 17GPa and dielectric constant is 6.
[0040] The SiCf-Si3N4-Si composite ceramic prepared by the present invention has a relative density of 95-99%, a bending strength of 400-600 MPa, a fracture toughness of 7-9 MPa·m 1 / 2 ), dielectric constant (5-8), indicating that the SiCf-Si3N4-Si composite ceramics have excellent mechanical properties (flexural strength, fracture toughness) and dielectric constant.
[0041] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A high-strength and high-toughness SiC f -Si3N4-Si composite ceramic, characterized in that The SiC f- Si3N4-Si composite ceramics are prepared by adding Si powder, Al2O3 powder and phenolic resin powder into anhydrous ethanol and mixing and ball-milling to obtain Si-Al2O3-phenolic resin impregnation slurry; the pretreated silicon carbide fiber cloth is completely immersed in the above impregnation slurry, and then vacuumized, a protective gas with a pressure of 4 to 10 MPa is introduced and the pressure is maintained, and the preform is dried and cured at 80 to 150° C., and the obtained preform is sintered at 1800 to 1900° C. under a nitrogen pressure of 1 to 10 MPa.
2. The high-strength and high-toughness SiC according to claim 1 f- Si3N4-Si composite ceramics, characterized in that: The relative density of the SiCf-Si3N4-Si composite ceramic is above 95%, the bending strength is 400-600MPa, and the fracture toughness is 7-9MPa·m 1 / 2 , hardness is 16~18GPa, and dielectric constant is 5~8.
3. The high-strength and high-toughness SiC according to claim 1 f- Si3N4-Si composite ceramics, characterized in that: The purity of the Si powder is above 99wt%, and the average particle size is 1-10μm; the purity of the Al2O3 powder is above 99.8wt%, and the particle size is 50-100nm; the purity of the phenolic resin powder is above 98wt%, and the average particle size is 10-50μm.
4. The high-strength and high-toughness SiC according to claim 1 f -Si3N4-Si composite ceramic, characterized in that The volume ratio of the Si powder, Al2O3 powder and phenolic resin powder is (20-30):(1-5):(1-5); the volume ratio of the total volume ratio of the Si powder, Al2O3 powder and phenolic resin powder to the pretreated silicon carbide fiber cloth is (11-20):(30-35).
5. The high-strength and high-toughness SiC according to any one of claims 1 to 4 f- The method for preparing Si3N4-Si composite ceramics is characterized in that: The steps include: S1. Si powder, Al2O3 powder and phenolic resin powder were added to anhydrous ethanol and mixed and ball-milled to obtain Si-Al2O3-phenolic resin impregnation slurry; S2. The pretreated silicon carbide fiber cloth is completely immersed in the Si-Al2O3-phenolic resin impregnation slurry, and then evacuated, a protective gas with a pressure of 4 to 10 MPa is introduced and the pressure is maintained, and dried and cured at 80 to 150 ° C to obtain a preform; S3. The preform is heated to 1800-1900°C and sintered under a nitrogen pressure of 1-10 MPa to obtain a high-strength and high-toughness SiC f -Si3N4-Si composite ceramics.
6. The high-strength and high-toughness SiC according to claim 5 f - A method for preparing Si3N4-Si composite ceramics, characterized in that: The ball milling speed in step S1 is 200-250 r / min, and the ball milling time is 24-36 h.
7. The high-strength and high-toughness SiC according to claim 5 f - A method for preparing Si3N4-Si composite ceramics, characterized in that: In step S2, the protective gas is nitrogen or argon; the pressure holding time is 30 to 60 minutes.
8. The high-strength and high-toughness SiC according to claim 5 f - A method for preparing Si3N4-Si composite ceramics, characterized in that: The heating rate in step S3 is 5-15° C. / min, and the sintering time is 1-4 h.
9. Application of the high-strength and high-toughness SiCf-Si3N4-Si composite ceramic according to any one of claims 1 to 4 in the field of preparing mobile phone back panels.
Citation Information
Patent Citations
Two-dimension fiber cloth-reinforced silicon nitride-silicon carbide ceramic composite material and preparation method thereof
CN103724032A
Fibre-reinforced ceramic and process therefor
EP0188270A2
Composite material and method for manufacturing it
GB2216143A
Formation of a ceramic composite by centrifugal casting
US5262366A
Cited By
High-toughness silicon carbide ceramic and production process thereof
CN120864898A
High-toughness silicon carbide ceramic and process for producing same
CN120864898B